Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) \(\left(2\sqrt{3}+\sqrt{5}\right)\sqrt{3}-\sqrt{60}\) = \(6+\sqrt{15}-2\sqrt{15}\)
= \(6-\sqrt{15}\)
b) \(\left(5\sqrt{2}+2\sqrt{5}\right)\sqrt{5}-\sqrt{250}\) = \(5\sqrt{10}+10-5\sqrt{10}\) = \(10\)
c) \(\left(\sqrt{28}-\sqrt{12}-\sqrt{7}\right)\sqrt{7}+2\sqrt{21}\) = \(14-2\sqrt{21}-7+2\sqrt{21}\)
= \(7\)
d) \(\left(\sqrt{99}-\sqrt{18}-\sqrt{11}\right)\sqrt{11}+3\sqrt{22}\)
= \(33-3\sqrt{22}-11+3\sqrt{22}\) = \(22\)
a)(2√3+√5)√3-√60
=6+√15-2√15
=6-√15
b)(5√2+2√5)√5-√250
=5√10+10-5√10
=10
c)(√28-√12-√7)√7+2√21
=14-2√21-7+2√21
=7
d)(√99-√18-√11)√11+3√22
=33-3√22-11+3√22
=22
\(=\sqrt{\left(\sqrt{3}+2\right)^2}-\sqrt{\left(2\sqrt{3}-1\right)^2}\)
\(=\sqrt{3}+2-2\sqrt{3}+1\)
\(=3-\sqrt{3}\)
b) \(\sqrt{\left(7-\sqrt{3}\right)^2}+\sqrt{\left(\sqrt{3}+1\right)^2}\)
\(=7-\sqrt{3}+\sqrt{3}+1\)
\(=8\)
\(A^2=3+\sqrt{5}+3-\sqrt{5}-2\sqrt{\left(3-\sqrt{5}\right)\left(3+\sqrt{5}\right)}\)
\(=6+2\sqrt{4}\)
\(=6+2.2\)
\(=10\).Mà ta thấy A<0 nên \(A=-\sqrt{10}\)